2020
DOI: 10.21203/rs.3.rs-40862/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Qualitative Evaluation of the General Practitioner Chronic Non-Communicable Diseases Training Programme

Abstract: Background: In China, general practitioners have limited ability to provide care for common chronic non-communicable diseases because they lack postgraduate training. In an attempt to improve general practitioners’ skills in this regard, the present authors previously launched the Chronic Non-Communicable Diseases Training Programme. The present study aims to evaluate the effectiveness of this programme.Methods: Thirty-nine trainee general practitioners who participated in the programme underwent semi-structur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In our study, it was demonstrated that training-related NCDs that CHWs have received was matched with the NCDs managed by them. Studies have showed that training could boost CHWs' working ability and self-con dence to be quali ed for NCDs management [41][42][43][44][45]. In this survey, it revealed that CHWs were not satis ed with the contents and forms of training in our region.…”
Section: Discussionmentioning
confidence: 76%
“…In our study, it was demonstrated that training-related NCDs that CHWs have received was matched with the NCDs managed by them. Studies have showed that training could boost CHWs' working ability and self-con dence to be quali ed for NCDs management [41][42][43][44][45]. In this survey, it revealed that CHWs were not satis ed with the contents and forms of training in our region.…”
Section: Discussionmentioning
confidence: 76%